Towards resolving taxonomic uncertainties in wolf, dog and jackal lineages of Africa, Eurasia and Australasia - Krofel, Miha; Hatlauf, Jennifer; Bogdanowicz, Wieslaw; Campbell, L. A. D.; Godinho, Raquel; Jhala, Yadvendradev; Kitchener, A. C.; Koepfli, K.-P.; Moehlman, P.; Senn, H.; Sillero-Zubiri, Claudio; Viranta, S.; et al. (Journal of Zoology, 2021)
Successful conservation depends on accurate taxonomy. Currently, the taxonomy of canids in Africa, Eurasia and Australasia is unstable as recent molecular and morphological studies have questioned earlier phenetic classifications. We review available information on several taxa of Old World and Australasian Canis with phylogenetic uncertainties (namely, African jackals, Asian wolves and Australasian dogs), in order to assess the validity of suggested scientific names and provide a scientific basis for reaching a taxonomic consensus primarily based on molecular data, but also including morphology, biogeography and behavioural ecology. We identify major knowledge gaps, provide recommendations for future research and discuss conservation implications of an updated taxonomic framework. Recent molecular studies indicate that the former Afro-Eurasian ‘golden jackal’ represents two distinct lineages, the golden jackal (Canis aureus) from Eurasia and the African wolf (C. lupaster) from Africa. Phylogenetic research also indicates that the side-striped and black-backed jackals form a monophyletic group that branched earlier than Canis, Cuon and Lycaon, which should be reassigned to the genus Lupulella as L. adusta and L. mesomelas, respectively. The Himalayan/Tibetan and Indian wolf lineages appear to have diverged earlier and are distinct from all other grey wolves (C. lupus) based on mitochondrial and nuclear genome data. However, until genome-wide data from multiple individuals across the range clarify relationships with other taxa, we suggest referring to the Himalayan/Tibetan wolf lineage as Canis lupus chanco. We support the currently accepted nomenclature for the Indian wolf Canis lupus pallipes for the wolf populations found on the Indian subcontinent and possibly also in south-western Asia (exact geographical boundary pending). The information presented here provides a current and consistent taxonomic framework for use by conservationists and other practitioners, but it is also intended to stimulate further ...